Trouble dans le gangsta-rap : quand des rappeuses s’approprient une esthétique masculine - Keivan Djavadzadeh (Genre, Sexualité et Société)
This article traces the process through which female rappers in the 1990s reclaimed gangsta-rap music, a genre that emerged in the 1980s. Gangsta-rap music ambivalently allowed some Black men to reach some forms of public recognition. The hypermasculinity it promotes can therefore be understood as a form of “protest masculinity”. Despite gangsta-rap sexual politics, some female rappers have decided to contribute to this subgenre of rap music because its aesthetic offered them new possibilities of expression and protest. Thus, gangsta-rap music can be analyzed as an arena of conflict and dialogue in which female rappers negotiate their identity by subverting gender and sexual norms. Through their gender performances, female gangsta-rappers challenge both the established gender order and men’s hegemony in gangsta-rap.